Agriculture and food security in Asia by 2030 - Kym Anderson; Anna Strutt (Asian Development Bank Institute (ADBI), 2012)
Rapid trade-led economic growth in emerging Asia has been shifting the global economic and industrial centres of gravity away from the north Atlantic, raising the importance of Asia in world trade but also altering the commodity composition of trade by Asia and other regions. What began with Japan in the 1950s and the Republic of Korea and Taipei,China from the late 1960s has spread to the much more populous ASEAN region, the People's Republic of China, and India. This paper examines how that growth and associated structural changes are altering agricultural markets in particular and thereby food security. It does so retrospectively and by projecting a model of the world economy that compares alternative growth strategies, trade policy scenarios and savings behaviors to 2030. Projected impacts on sectoral shares of gross domestic product (GDP), "openness" to trade and the composition and direction of trade are drawn out, followed by effects of the boom in non-farm sectors on agricultural self-sufficiency and real food consumption per capita in Asia and elsewhere. The paper concludes by drawing implications for policies that can address more efficiently Asia's concerns about food security and rural-urban income disparity than the trade policy measures used by earlier-industrializing Northeast Asia.
Keywords: D58; F13; F15; F17; Q17; 330; asia; asean; agricultural markets; agriculture; food security; world trade; Ernährungssicherung; Landwirtschaftliche Entwicklung; Exportinduziertes Wachstum; Agraraußenhandel; Wirtschaftspolitik; Asien